Overexpression of Epigen during Embryonic Development Induces Reversible, Epidermal Growth Factor Receptor-Dependent Sebaceous Gland Hyperplasia - Dahlhoff, Maik (American Society for Microbiology, 2014)
The epidermal growth factor receptor (EGFR) system is a key regulator of epithelial development and homeostasis. Its functions in the sebaceous gland (SG), however, remain poorly characterized. In this study, using a transgenic mouse line with tissue-specific and inducible expression of the EGFR ligand epigen, we showed that increased activation of the EGFR in skin keratinocytes results in enlarged SGs and increased sebum production. The phenotype can be reverted by interrupting transgene expression and is EGFR dependent, as gland size and sebum levels return to normal values after crossing to the EGFR-impaired mouse line Wa5. Intriguingly, however, the SG enlargement appears only if EGFR activation occurs before birth. Importantly, the enlarged sebaceous glands are associated with an increased expression of the transcription factor MYC and of the transmembrane proteins LRIG1, an established negative-feedback regulator of the EGFR/ERBB tyrosine kinase receptors and a stem cell marker. Our findings identify EGFR signaling as a major pathway determining SG activity and suggest a functional relationship between the EGFR/ERBB system and MYC/LRIG1 in the commitment of stem cells toward specific progenitor cell types, with implications for our understanding of their role in tissue development, homeostasis, and disease.